Numerical Analysis and Model tests of the Bearing Capacity of shallow Strip Footing resting on Multi-layered Soils - حسن, مالك; حلوم, ولاء (Latakia University Journal -Engineering Sciences Series, 2020)
Naturally occurring soils are often deposited in layers. Within each layer the soil may, typically, be assumed to be homogeneous, although the strength properties of adjacent layers are generally quite different. If a foundation is placed on the surface of a layered soil for which the thickness of the top layer is large compared with the width of the foundation, then realistic estimates of the bearing capacity may be obtained using conventional bearing capacity theory. however, this approach may not be appropriate, If the thickness of the top layer is not large compared to width of the footing. In present investigation attempt has been made to study the bearing capacity and settlement characteristics of footings subjected to central vertical load and resting on layered soil with the help of model tests and with the application of finite element method (FEM) to calculate bearing capacity of a strip footing on one-layer and two-layer soil (Sand and Clay). To investigate the effect of various parameters on soil bearing Capacity a commercial finite element software, PLAXIS, has been used. Soil profile contains two soil types including sand and clay. Soil behavior is represented by the elasto-plastic Mohr-coulomb (MC) -model. For a one-layer case, the bearing capacity also is calculated which has a good agreement with theoretical equations. For a layered soil, soft-over strong soil, parametric study was carried out. It is concluded that the bearing capacity of footing decreases as the height of clayey soil increases whilst the displacement under footing increases. There is a critical depth where the stronger bottom layer does not affect ultimate bearing capacity and failure mechanism of footing.